2021
DOI: 10.4314/ejhs.v31i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Examination of Trichomonas vaginalis Infection and Risk of Prostate Cancer in the Biopsy of Patients with Different Prostate Lesions

Abstract: BACKGROUND፡ Trichomoniasis is a sexually transmitted infectious disease caused by a flagellated protozoa, Trichomonas vaginalis (T.vaginalis) and is often asymptomatic in men. Benign prostatic hyperplasia (BPH) and prostate cancer (PCA) are the most common urological diseases in the elderly. Scientists have proposed various factors which trigger prostate cancer, including sexually transmitted diseases. Thus, this study aimed to evaluate the potential role of T. vaginalis as a risk factor for various prostate l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…T. vaginalis infection in the urogenital tract could display distinct phenotypes. [ 18 ] However, the current adult patient was an extremely rare case. On the one hand, previous reports showed that pulmonary T. vaginalis infection mainly occurred in neonates due to maternal infection.…”
Section: Discussionmentioning
confidence: 99%
“…T. vaginalis infection in the urogenital tract could display distinct phenotypes. [ 18 ] However, the current adult patient was an extremely rare case. On the one hand, previous reports showed that pulmonary T. vaginalis infection mainly occurred in neonates due to maternal infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is worthy of note to mention the established relationship between a complication (urinary tract infections) stemming from the incidence of BPH and sexually transmitted diseases (STDs) (Kamarkhani et al, 2021), because more often than not, medicinal plants used in the treatment of Sexually Transmitted Infections (STIs) have been utilized in the management of BPH. These medicinal plants have been reported to contain phytohormones and other pharmacologically active constituents that have ameliorated the incidence of BPH (Chen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…An Egyptian study, involving 445 men, identified that while only 8.3% of controls were seropositive for trichomoniasis, this proportion rose to 19% in PC patients, and was associated with PSA levels and tumor stage; however, no impact on prognosis or mortality was observed (p<0.001 and p<0.05) (Saleh et al, 2020). In Iran, 250 samples of prostate lesions were analyzed using PCR, all were negative; however, studies that reported associations between these two factors used serology for T. vaginalis, thus PCR may not be the most appropriate technique to determine an association (Kamarkhani et al, 2021).…”
Section: Case-control Studiesmentioning
confidence: 99%